Contribution of the Digital Facebow and Individually Programmed Articulator in Removable Complete Dentures - Z. Kadlec; Ľ. Harvan; E. Jurásková Sedlatá; M. Eber (Czech Dental Chamber, 2015)
Introduction and aim: It is a generally known fact, that in most of the English books of prosthetic dentistry, the knowledge of gnathology and its accessories including the registration of central relation are essential for the making of high quality removable complete dentures. The question remains, how sophisticated must these accessories be? It seems so far, that the mechanical face bow and semiadjustable articulator are enough for making the removable complete dentures, and the digital face bow with the individually programmed articulator make the work better and more precise. Material and methods: 115 complete dentures were made, 90 of these were made on the basis of the Gerber's concept with the mechanical face bow and semiadjustable articulator, 25 dentures were made with the use of digital face bow and individually programmed articulator. The concept of bilateral balanced occlussion as well as the subjective assessments of the patients were evaluated. Results and conclusion: The result for clinical practice was that the use of semiadjustable articulator with a suitable face bow was completely adequate for the making of complete dentures, with taking into consideration the correct registration of intermaxillary relation, which is the central relation.